Gambaran Faktor-Faktor Kepatuhan Minum Obat dalam Pelaksanaan POPM Filariasis di Kabupaten Semarang (Studi di Wilayah Kerja Puskesmas Gedangan Kecamatan Tuntang) - Fania Maulida Layli; Mateus Sakundarno Adi; Lintang Dian Saraswati; Praba Ginandjar (Jurnal Kesehatan Masyarakat (Undip), 2020)
Gedangan’s Health Center is one of the health centers in the Semarang Regency, which in the implementation of the MDA filariasis didn’t reach the coverage filariasis prevention drugs intake from the target population with 83.6% and 83.8%. To increase the coverage required community compliance in taking that drugs, therefore the study aimed to describe the factors of compliance in implementing MDA filariasis in the working area of the Gedangan’s Health Center. This was a rapid survey with a cross-sectional approach, with a study population of 21.380 people. The first stage selecting 30 clusters with PPS (Proportion Population Size) and then selecting 7 subjects from each cluster with simple random sampling. The sample size in this study was 210 people. The result showed 69.5% of respondents complied prevention drugs of filariasis. The proportion of compliant respondents is greater in the age group 26-45 years (74.7%), female (72.1%), low education level (84.6%), employed (84,6%), good level of filariasis knowledge ( 73.3%), good level of MDA knowledge (79%), receiving filariasis cadres support (88.2%), receiving social support (92.1%), and haven’t experience any side effects (84.6%). In conclusion, the age group 26-45 years old, female, low education level, employed, good level of filariasis and MDA knowledge, receiving filariasis cadres support, receiving social support and haven’t experience any side effect, more compliant of taking preventive drugs of filariasis. Although in this study, the filariasis cadres support was less than optimal.